(3HOGFY GdSdc aj WHGFY Gdedcs - (3CHh YHO Gddg TeS GdOjf eMeO Hf Ydj Hf eMeO GdGUHMj GdCfOdSj, GHf GdGRQb,J (B896 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGdc Gdedc GjLGOkG hJbOjQkG CeG HYO aEf ef CTgQ eG Yde YbdkG hSeYkG aUQJ Edi JdNjU eG cJH GdfGS ai Gdedc hGdGeGQI s
(3BNQgG (B:s
(3Cf ef Cgd GdOhd ef MGhd GJHGY ef bHdg ai gPG GdHGH ai abfY HeG HdZJ Edjg bOQJg ceG jMci Cf GdMLGL s
(3YdjgG JedcGJs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdSjGSI hGdGLJeGYs